Academic Subject Problem: Epistemological Crisis and Its Overcoming - M. B. Sapunov; A. A. Polonnikov (Высшее образование в России)
The paper focuses on the analysis of ontological, epistemological and pedagogical terms of changes in education, first of all – on the status of an academic subject. From the ontological perspective, they are related to transfer from “object” ontology to communication-and-activity one, in terms of epistemological approach – from naturalism to transcendentalism, whereas with regard to pedagogical perspective – from autocratic-disciplinary organization of the academic process to a student-oriented pattern. The first part of the article describes academic subject’s functions in the process of educational reproduction. An academic subject is interpreted not so much from the perspective of the knowledge it contains, but as a complex linguistic code which organizes and regulates educational interaction. Its basics and structure, a mechanism of constituting educational reality are described, as well as the design specifics that hamper changes in education. The authors dwell on the distinction between an academic and scholarly subject. Part two of the article contains criticism of an academic subject practice in the university education. The central event here is attributed to differentiation and diversification of the form of academic subject, disintegration of its integrity into local autonomous linguistic fields. The conclusion formulates the idea how to overcome an academic subject crisis, which heart is discursive transformation of its representation practice. Based on Gilles Deleuze’s ideas, the authors consider the transformation of discursive practices in which an academic subject is embodied to be the condition for education change.